Clickbait Content Titles on Internet Media Reviewed from Criminal Law Perspective - Diandra Alya Sayyidina; Gelar Ali Ahmad (Universitas Negeri Surabaya, 2024)
This study examines the legal aspects of clickbait content titles, a common strategy used by creators to attract user attention and generate profit. While effective in increasing traffic, clickbait often misleads users, degrades internet content quality, and causes economic and experiential harm. Using a juridical normative method with legislative and conceptual approaches, the study collects legal materials through the snowball method, starting from selected literature that expands over time. The findings reveal that although some existing laws can be indirectly applied to address clickbait practices, none explicitly prohibit or regulate them. The lack of clear legal norms and the absence of criminal sanctions contribute to creators’ indifference toward the negative impacts of clickbait. As a result, current regulations are insufficient to deter such practices. To overcome this legal gap, the study recommends criminalization through either the drafting of new legislation or amendments (addendums) to existing laws. This includes the need for detailed regulatory frameworks, the inclusion of explanatory notes, and the implementation of appropriate criminal sanctions. Clear and specific rules are essential to provide legal certainty and serve as a reference for law enforcement, ultimately reducing the recurrence of harmful clickbait practices in digital media.